2021
DOI: 10.17221/39/2021-jfs
|View full text |Cite
|
Sign up to set email alerts
|

The influence of growing medium composition on pine and birch seedling response during the period of simulated spring drought

Abstract: Climate change increases the earliness and effect of spring dry spells. The efforts to reduce their negative effects on tree regeneration include improvement in physical properties of soil aimed at an increase in water retention and availability. Clinoptilolite from the group of zeolites belongs among such water-absorbent natural materials. The article aims to assess the effect of clinoptilolite admixture in a growing medium, along with different fertilizer concentration, on the growth of pine and birch seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Different studies evaluated the effect of different growing media on the growth performance of different plants (Abbadi 2017a;Abbadi 2017b;Abbadi et al 2017;Abbadi et al 2019). Other investigators also confirmed the importance of the selection of an appropriate growth medium for better growth at different stages (Špulák and Hacurová 2021;Madhavi et al 2021). A growing media consist of three components i.e.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Different studies evaluated the effect of different growing media on the growth performance of different plants (Abbadi 2017a;Abbadi 2017b;Abbadi et al 2017;Abbadi et al 2019). Other investigators also confirmed the importance of the selection of an appropriate growth medium for better growth at different stages (Špulák and Hacurová 2021;Madhavi et al 2021). A growing media consist of three components i.e.…”
Section: Introductionmentioning
confidence: 92%
“…This combination was found good for vigorous growth and a stronger root system (Gil et al 2012). Špulák and Hacurová (2021) investigated the influence of growing medium composition on pine and birch seedling response during the period of simulated spring drought. Results of this study showed that the birch responded more intensively to the fertilizer concentration than to the clinoptilolite admixture and was more vulnerable to drought damage.…”
Section: Introductionmentioning
confidence: 99%